STUDI TENTANG USAHA TANAMAN HIAS DI KELURAHAN LUBUK MINTURUN SUNGAI LAREH KECAMATAN KOTO TANGAH KOTA PADANG - Nengsih, Fetri Silvia (STKIP PGRI Sumbar, 2014)
Lubuk minturun lareh river village chief is fertile agri culture area, so very correct to by decoration plant area. The purposes of research are to get data, to process, to analize, and to discuss of study about effort of decoration plant in Lubuk Minturun lareh river village chief Koto Tangah subdistrict Padang city are seem from : 1) Financial capital, 2) Marketing, 3) Income, 4) Kinds of decoration, 5) Haw to seeding, 6) Total of man power.The research appertain descriptive research, to be population of this research that society do in effort of decoration plant sector enter decoration plant farmer community. Sample from this research are taken like Total Sampling, the serearch of sample amount to 67âsperson, data collection use closed quitionnaire and the analize is used persentation.The result of research are addressed to : 1. Firs financial capital is the is self financial capital, financial capital great are more than Rp 10.000.000, 2. Marketing manner are marketing with plump in area and pass through other people, abstacle are decoration plant cost is diffrent from each region, 3. Income total one mounth more than Rp 1.000.000 â Rp 1.999.000, expulsion total one mounth more than Rp 1.500.000 â Rp 1.999.000, 4. Kind of decoration plant are traded decoration plant as flower, leaf, and pot, consumerâs reason or community interest kind of decoration plant because beautiful, unique, and itâs easy treatment, 5. How to seeding are seeding like generative and vegetative, 6. Total of man power constant are more than 7-10 person.